2022
DOI: 10.1111/1759-7714.14697
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of poor predictive factors in extensive stage small cell lung cancer under etoposide‐platinum‐atezolizumab treatment

Abstract: Background: The phase III trial IMpower133 showed that platinum and etoposide plus atezolizumab was associated with improved overall survival (OS) and progression free-survival (PFS) when compared to the placebo group in treatment-naïve extensive stage (ES) small cell lung cancer (SCLC). Due to superiority in clinical outcomes, combination immunotherapy plus chemotherapy have become mainstay treatment modalities as first-line treatment in ES-SCLC. Nevertheless, real-world data are still lacking and the search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 34 publications
5
6
0
Order By: Relevance
“…Therefore, elevated serum LDH levels may re ect increased cancer cell activation and are associated with poor prognosis in cancer patients [28]. The results of our study are compatible with those of previous studies [17,21,22,[26][27][28][29], and LDH was identi ed as a factor associated with unfavorable outcomes in extensive-stage SCLC patients who received rst-line anti-PD-L1 ICIs combined with chemotherapy.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, elevated serum LDH levels may re ect increased cancer cell activation and are associated with poor prognosis in cancer patients [28]. The results of our study are compatible with those of previous studies [17,21,22,[26][27][28][29], and LDH was identi ed as a factor associated with unfavorable outcomes in extensive-stage SCLC patients who received rst-line anti-PD-L1 ICIs combined with chemotherapy.…”
Section: Discussionsupporting
confidence: 89%
“…The serum LDH concentration is another prognostic factor frequently identi ed in patients with malignancies [17,21,22,26,27]. LDH is an essential enzyme in glycolysis and functions in catalyzing the conversion of pyruvate to lactate; elevated serum LDH levels have been used as an in ammatory index [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In stratified analysis, we found that ES-SCLC patients with normal LDH value benefit more from ICI than patients with abnormally high LDH levels; this is consistent with Lim et al [ 30 ].. A previous study suggested that LDH might be an indicator of tumor burden and that increased LDH inhibits antitumor activity of immune checkpoints by altering metabolism, nutrient availability, and acidic microenvironment [ 31 ]. In CheckMate-331, among SCLC patients with below-normal LDH, OS tended to be longer in patients receiving nivolumab as second-line treatment than in patients receiving chemotherapy [ 26 ].…”
Section: Discussionsupporting
confidence: 88%
“… 18 , 19 Although ES‐SCLC has traditionally had a poor prognosis, recent phase three trials have confirmed improved outcomes with the addition of ICIs to chemotherapy. 8 , 9 , 11 , 20 However, only a few retrospective studies reported the survival outcomes in the real world, some without control groups, 21 , 22 some with insufficient case numbers, 23 , 24 and some including only PD‐L1 inhibitors. 25 , 26 , 27 Concerns about the inconsistency of anti‐PD‐1 agents and anti‐PD‐L1 agents suggested by the consequences of clinical trials are inconclusive.…”
Section: Discussionmentioning
confidence: 99%